Weight optimization of an enclosed stressed skin derrick designed for Arctic regions - Ringsberg, Jonas; Hu, ZhiQiang (2019)
The study presents a design procedure and how it is applied to design a new type of enclosed stressed skin derrick structure which improves the working environment for the crew and protects the drilling and pipe handling equipment against harsh conditions that may prevail in the Arctic. The new design is compared against a conventional truss derrick structure with regards to the weight of the structures, their locations of the center of gravity (for stability conditions), and material and manufacturing costs. In comparison with the reference truss derrick structure, for the same design loads, the new derrick structure has 21% lower weight, 5% lower center point of gravity, and 11% lower material and manufacturing and cost.